PENGARUH HARGA, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP MINAT BELI JERSEY FUTSAL KISIROSARI DI KOTA KEDIRI - Ahmad Muzakki Alfaqih; Abu Talkah; Arisyahidin Arisyahidin (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aimed to examine the effect of price, product design, and product quality on buying interest in Gratingro Sari futsal jersey in Kediri. The sample of this study were players of the futsal team in the city of Kediri. The analysis technique used was multiple linear regression analysis, with a total sample of 100 respondents using purposive random sampling method. The results of data analysis and hypothesis testing show that price, product design and product quality have a significant effect on buying interest in futsal jersey. The results showed that price, product design and product quality increased consumer purchase interest.